YouTube as a resource for evaluating the unmet needs of caregivers of stroke survivors. (September 2020) - Denham, Alexandra MJ; Baker, Amanda L; Spratt, Neil J; Wynne, Olivia; Hunt, Sally A; Bonevski, Billie; Kumar, Ratika
Content produced by caregivers of stroke survivors on the online video-sharing platform YouTube may be a good source of knowledge regarding caregivers' unmet needs. We aimed to examine the content, quantity and quality of YouTube videos that target and discuss the needs and concerns of caregivers of stroke survivors. YouTube was systematically searched using six search strings, and the first 20 videos retrieved from each search were screened against the inclusion criteria. A pre-determined coding schedule was used to report the rate of unmet needs in each video. Twenty-six videos were included in the analysis. In total, 291 unmet needs were reported by caregivers of stroke survivors, an average of 11.2 unmet needs per video. The most common unmet needs domain was 'Impact of Caregiving on Daily Activities' (44%). Most videos were developed in the United States (61.5%) and featured spouses of stroke survivors (65.47%). Content produced by caregivers of stroke survivors on YouTube may be used as a tool for caregivers to provide and receive support through online communication. YouTube videos offer insight into the unmet needs of caregivers of stroke survivors and may be used as an additional resource for stroke services to support caregivers.